Auditor Reputation, Complexity, Auditor Switching, and Audit Tenure Effects on Audit Report Lag, With Auditor Gender as Moderator - Rahul Yaner; Zulhelmy (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This research aims to determine the effect of auditor reputation, company operational complexity, auditor switching, and audit tenure on audit report lag with auditor gender as a moderating variable. This research uses a quantitative approach with a research population of consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. The analytical method used is moderated regression analysis (MRA) on panel data, using Eviews 12. The research results show that auditor switching has a positive effect on audit report lag. However, auditor reputation, company operational complexity, and audit tenure do not affect audit report lag. Meanwhile, auditor gender does not moderate the effects of the independent variables on the audit report. This study presents essential implications for regulators, companies, and audit practitioners. First, auditor switching significantly increases audit report lag, highlighting the need for strategic planning in transitions. Second, the minimal impact of auditor reputation, operational complexity, and tenure confirms that audit efficiency is largely driven by standardized procedures, advanced technology, and strong quality control systems. Lastly, the absence of a moderating effect of auditor gender indicates that professional standards and training effectively minimize behavioral differences. This study offers originality by demonstrating that, within a highly standardized audit environment, auditor switching remains the only significant determinant of audit report lag, while auditor gender does not function as a moderating factor, thereby challenging both agency theory and social role theory assumptions in the context of modern auditing practices